Ageing, Temporality and Performance: Joan Rivers' body of work. (3rd April 2019) - Mock, Roberta
Abstract : Joan Rivers' performance in the public sphere revolved around the visibility and cultural inscription of an ageing and older woman. Linking aesthetic, professional and physiological processes, her body, work and performance merged as and in an extended and finite professional practice. A pioneer of stand-up comedy as a genre, and one of its most significant and visible female practitioners, Rivers is known for her aggressive and often outrageous wit, which was directed at both herself and other celebrities, as well as her extensive plastic surgeries. When she died in 2014, at the age of 81, she was still fully engaged in a relentless schedule of live performances and televised appearances. By then, Rivers was well established as an ubiquitously present elder who refused to conform to long-standing stereotypes of asexuality, able to thrive in a rapidly shifting cultural landscape of surgically enhanced bodies, surveillance as entertainment and public confession. At the heart of the discussion in this article is the spatio-temporality of the performing body, borrowing from Maurice Merleau-Ponty's understanding of the body as a 'nexus of living meanings' and Jacques Derrida's development of Merleau-Ponty's use of the term 'invagination' to embrace generic textual strategy. In stand-up as a genre, both originality and continuity are paradoxically valued by audiences in equal measure. Success – that is, laughter – is largely determined by the extent to which these align coherently with the comedian's bodily presence and her onstage social, cultural and/or political positioning. Focusing primarily on the expression of Rivers' persona via a variety of mutually reinforcing cultural texts in the final three years of her life, this article analyses how her performing body in every medium was importantly always made present through its sexual difference and attendant gendered ageing processes.